Vibrational signature of water molecules in asymmetric hydrogen bonding environments - Zhang, Chao; Khaliullin, Rustam Z.; Bovi, Daniele; Guidoni, Leonardo; Kühne, Thomas D. (Journal of Physical Chemistry Letters, 2013)
The O-H stretching vibrational modes of water molecules are sensitive to their local environments. Here, we applied effective normal-mode analysis to isolate contributions of each of the two hydrogen atoms to the vibrational modes ν1 and ν3 of water molecules in the liquid phase. We demonstrate that the decoupling of the two contributions fd and the frequency splitting of the vibrational modes Δω13 are inextricably related to the symmetry of the hydrogen bonding environment. We show that ambient liquid water modeled at the density functional level of theory exhibits the characteristics of an asymmetric environment with an average decoupling of 0.82 and a splitting of 137 inverse centimeters. Such large value of decoupling and splitting would account for the inhomogeneous broadening as observed in the vibrational spectra of liquid water. The computational protocols and the results of this work will facilitate the interpretation of experimental Raman and infrared spectra of interfacial water molecules at hydrophobic, membrane, and protein surface. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: ab initio molecular dynamics; inhomogeneous broadening; interfacial water; liquid water; vibrational analysis